2019
DOI: 10.1097/rlu.0000000000002668
|View full text |Cite
|
Sign up to set email alerts
|

18F-PSMA 1007 Brain PET/CT Imaging in Glioma Recurrence

Abstract: A 64-year-old man with a known case of right parietal lobe glioblastoma multiforme operated on in August 2018 was referred for 18F-FDG PET/CT with a clinical suspicion of recurrence. He underwent 18F-FDG and 18F-PSMA 1007 scans. Both the scans showed intense tracer uptake in right parietal lobe lesion, which concurred with MRI findings of recurrent disease and was later proven on histopathologic examination as recurrence. Our case highlights the feasibility of 18F-PSMA 1007 PET/CT imaging of suspected glioblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…Several pilot studies with each a few patients included have demonstrated the general feasibility of non-invasive assessment of PSMA expression in glioblastoma via PET imaging (34,(40)(41)(42)(43). Whereas those case series have used either 68 Ga-labeled PSMA tracers such as 68 Ga-PSMA-11 or less common PSMA-directed tracers such as 18 F-DCFPyL or 89 Zr-Df-IAB2M, a recent case report for the first time demonstrated the feasibility of 18 F-labeled PSMA PET imaging in a glioblastoma patient (44). Several advantages of required, have started an incipient shift from 68 Ga-to 18 F-labeled PSMA-targeted tracers in PET imaging of prostate cancer as well (45).…”
Section: Discussionmentioning
confidence: 99%
“…Several pilot studies with each a few patients included have demonstrated the general feasibility of non-invasive assessment of PSMA expression in glioblastoma via PET imaging (34,(40)(41)(42)(43). Whereas those case series have used either 68 Ga-labeled PSMA tracers such as 68 Ga-PSMA-11 or less common PSMA-directed tracers such as 18 F-DCFPyL or 89 Zr-Df-IAB2M, a recent case report for the first time demonstrated the feasibility of 18 F-labeled PSMA PET imaging in a glioblastoma patient (44). Several advantages of required, have started an incipient shift from 68 Ga-to 18 F-labeled PSMA-targeted tracers in PET imaging of prostate cancer as well (45).…”
Section: Discussionmentioning
confidence: 99%
“…PSMA expression was found in endothelial cells associated with neovascularization and, for these reasons, can be a very interesting marker for monitoring anti-angiogenic drugs [314] At the moment, only few studies evaluating PSMA targeted imaging of gliomas/glioblastomas in clinical practice are currently available. Moreover, most of these studies are case reports or case series [255][256][257][258][259][260][261][262][263][264]315]. Although limited, these studies confirmed that high-grade glioma/glioblastoma are PSMA-avid compared to low-grade and PSMA radioligand mainly binds vascular endothelial cells.…”
Section: Other Targets Of Tumour Microenvironmentmentioning
confidence: 84%
“…At the moment, only few studies evaluating PSMA targeted imaging of gliomas/glioblastomas in clinical practice are currently available. Moreover, most of these studies are case reports or case series [ 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 315 ]. Although limited, these studies confirmed that high-grade glioma/glioblastoma are PSMA-avid compared to low-grade and PSMA radioligand mainly binds vascular endothelial cells.…”
Section: In Vivo Imaging For the Study Of Gbm Heterogeneity And MImentioning
confidence: 99%
“…On reviewing the titles and abstracts, 117 articles were excluded because the reported data were not within the field of interest of this review. 10 articles were selected and retrieved in full-text version [ 15 - 24 ]; no additional studies were found when screening the references of these articles. In total, 10 articles were included in the systematic review [ 15 - 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only a few studies evaluating PSMA-targeted imaging of gliomas/glioblastomas in clinical practice are currently available. Moreover, most of these studies are case reports or case series [ 15 , 17-19, 21- 24 ] probably because few centers currently use radiolabeled PSMA PET/CT or PET/MRI, thereby reducing the population of patients analyzed globally. As a consequence, considering a very low number of reports and patients analyzed, no high quality evidence could be drawn about the role of radiolabeled PSMA in gliomas/glioblastomas; further, large prospective studies are needed to clarify the real clinical and diagnostic role of the radiolabeled PSMA in this field and its possible position in the diagnostic flow-chart.…”
Section: Discussionmentioning
confidence: 99%